Gene clusters for biosynthesis of mycosporine‐like amino acids in dinoflagellate nuclear genomes: Possible recent horizontal gene transfer between species of Symbiodiniaceae (Dinophyceae). Issue 1 (26th November 2021) - Shoguchi, Eiichi
Abstract : Global warming increases the temperature of the ocean surface, which can disrupt dinoflagellate‐coral symbioses and result in coral bleaching. Photosynthetic dinoflagellates of the family Symbiodiniaceae include bleaching‐tolerant and bleaching‐sensitive coral symbionts. Therefore, understanding the molecular mechanisms for changing symbiont diversity is potentially useful to assist recovery of coral holobionts (corals and their associated microbes, including multiple species of Symbiodiniaceae), although sexual reproduction has not been observed in the Symbiodiniaceae. Recent molecular phylogenetic analyses estimate that the Symbiodiniaceae appeared 160 million years ago and diversified into 15 groups, five genera of which now have available draft genomes (i.e., Symbiodinium, Durusdinium, Breviolum, Fugacium, and Cladocopium ). Comparative genomic analyses have suggested that crown groups have fewer gene families than early‐diverging groups, although many genes that were probably acquired via gene duplications and horizontal gene transfers (HGTs) have been found in each decoded genome. Because UV stress is likely a contributor to coral bleaching, and because the highly conserved gene cluster for mycosporine‐like amino acid (MAA) biosynthesis has been found in thermal‐tolerant symbiont genomes, I reviewed genomic features of the Symbiodiniaceae, focusing on possible acquisition of a biosynthetic gene cluster for MAAs, which absorb UV radiation. On the basis of highly conserved noncoding sequences, I hypothesized that HGTs have occurred among members of the Symbiodiniaceae and have contributed to the diversification of Symbiodiniaceae–host relationships. Finally, I proposed that bleaching tolerance may be strengthened by multiple MAAs from both symbiotic dinoflagellates and corals.